Mitotic recombination of yeast artificial chromosomes. - Ragoussis, I; Trowsdale, J; Markie, D (1992)
Large regions of human DNA can be cloned and mapped in yeast artificial chromosomes (YACs). Overlapping YAC clones can be used in order to reconstruct genomic segments in vivo by meiotic recombination. This is of importance for reconstruction of a long gene or a gene complex. In this work we have taken advantage of yeast protoplast fusion to generate isosexual diploids followed by mitotic crossing-over, and show that it can be an alternative simple strategy for recombining YACs. Integrative transformation of one of the parent strains with the construct pRAN4 (containing the ADE2 gene) is used to disrupt the URA3 gene contained within the pYAC4 vector arm, providing the markers required for forcing fusion and detecting recombination. All steps can be carried out within the commonly used AB1380 host strain without the requirement for micromanipulation. The method was applied to YAC clones from the human MHC and resulted in the reconstruction of a 650 kb long single clone containing 18 known genes from the MHC class II region.